Komunikasi Inovasi Dalam Pelayanan Publik Kecamatan Beji Kota Depok - Alamsyah, Alamsyah; Pranawukir, Iswahyu; Sukma, Agus Hitopa; Misnan, Misnan; Suandi, Fikry (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to analyze and understand the application of innovative communication in public services in Beji District, Depok City. A qualitative approach was used with data collection methods through interviews, observation and documentation studies. The collected data was analyzed systematically to gain an in-depth understanding of relevant aspects of innovation communication in the context of public services in Beji District. The research results show that there are several innovative communication initiatives that have been implemented in public services in Beji District, such as the use of social media, mobile applications, and providing information online. This innovative communication helps increase accessibility, transparency and public participation in obtaining information and utilizing public services. However, there are challenges that need to be overcome, such as the lack of public awareness of these innovative initiatives. Therefore, further efforts are needed to increase public understanding and participation in the communication of innovation in public services. This research makes an important contribution to the understanding of innovation communication in the context of public services at the local level and can be a basis for the development of more effective communication strategies in the future